The model of professionally oriented patriotic education of future specialists of the defense industry - N. Ustinova (Вестник Северо-Кавказского федерального университета, 2022)
The article defines the importance of patriotic education of the modern generation of youth. The need for the formation of patriotism among students studying in the defense specialties of universities, which is distinguished by an orientation towards the specifics of future professional activity, defined as professionally oriented patriotism, is shown. The model of education of professionally oriented patriotism of students at the university is proposed, which allows to carry out purposeful educational activities in a complex way, taking into account the conditions of professional training of future specialists in the defense industry. The structure of the model contains five blocks connected by purpose, tasks, and content. The specificity of the model is determined by the characteristics of the professional activities of university graduates associated with the military-industrial and defense spheres.